E-Learning of Tafsir Al-Quran Course: A Study on Students’ Satisfaction towards Teaching Techniques and Assessment Methods - Ibrahim, Mohamed Akhiruddin (Advances in Social Sciences Research Journal, 2020)
During COVID-19 pandemic, Malaysia had implemented Movement Control Order (MCO) that disallowed usual face-to-face lectures in all education institutions. This compliance has affected both public and private higher education institutions in providing learning sessions to students. Thus, e-learning which is the implementation of teaching and learning sessions through technology systems is the best alternative to ensure that learning sessions are continuously uninterrupted. Part of the successful implementation of this learning method is influenced by teaching techniques and assessment methods. Therefore, the aim of this study is to know the students’ satisfaction towards teaching techniques and assessment methods in e-learning of Tafsir al-Quran course. Method used in this research is quantitative design whereas a semi-structured questionnaire distributed among 2nd year students of Quran and Multimedia Studies Program, Faculty of Quran and Sunnah Studies, Universiti Sains Islam Malaysia. This questionnaire has to be answered via Microsoft Forms and the data obtained then were analyzed descriptively through computer software namely Microsoft Excel and Statistical Package for Social Sciences (SPSS) version 25. The results of the study found that the level of students’ satisfaction towards teaching techniques and assessment methods in e-learning of Tafsir al-Quran course were at a good and satisfactory level. In this regard, teaching techniques applied by lecturers are very important in providing understanding to students, as well as a systematic assessment methods to identify the level of students’ understanding.